Magneto-Optics of a Weyl Semimetal beyond the Conical Band Approximation: Case Study of TaP - Polatkan, S.; Goerbig, M. O.; Wyzula, Jan; Kemmler, R.; Maulana, L. Z.; Piot, B. A.; Crassee; Akrap, Ana; Shekhar, Chandra; Felser, Claudia; Dressel, Martin; Pronin, Artem V; et al. (Physical Review Letters, 2020)
Landau-level spectroscopy, the optical analysis of electrons in materials subject to a strong magnetic field, is a versatile probe of the electronic band structure and has been successfully used in the identification of novel states of matter such as Dirac electrons, topological materials or Weyl semimetals. The latter arise from a complex interplay between crystal symmetry, spin-orbit interaction, and inverse ordering of electronic bands. Here, we report on unusual Landau-level transitions in the monopnictide TaP that decrease in energy with increasing magnetic field. We show that these transitions arise naturally at intermediate energies in time-reversal-invariant Weyl semimetals where the Weyl nodes are formed by a partially gapped nodal-loop in the band structure. We propose a simple theoretical model for electronic bands in these Weyl materials that captures the collected magneto-optical data to great extent.
CRIS-Team Scopus Importer:2022-04-14